The Design Museum of Mount Sinabung with Neo-Vernacular Architecture Approach - Wahyuni Zahrah; Ade Syahputra Astono (International Journal of Architecture and Urbanism, 2019)
Mount Sinabung is a volcano on the plateau of Karo Regency, North Sumatra, Indonesia. Mount Sinabung suddenly erupted in 2010. The last eruption of the volcano occurred since February 19, 2018, and until now become an attraction to find out more about volcanic disasters. Museum Mount Sinabung is present to provide the means for education, dissemination of information in the aspect of the volcano and geological disaster with recreative and educative of nature. The problem raised was "How to design a volcano museum using the neo-vernacular architectural approach?". By applying one flow that develops in this post-modern era to revive memories of a semi-historical culture, representational, plural and eclectic cultural Agenda on to evoke the Design of Museum Mount SinabungIn the application of the neo-vernacular architectural approach to the building of the Museum, the principle of building the Siwaluh Jabu is restored, physically and non-physically.By using the qualitative method of designing the Museum, it was designed because it was rational and planned systematically with the selected location. So, the Museum is conceptualized with a flexible gallery that can be used as a shelter for refugees. Thus, it is expected that the Museum can be a recreational-educational facility and as a means of supporting disaster mitigation.